Guide :

# Evaluate ;Find 3x2 - y3 - y3 - z if x = 3, y = -2, and z = -5.

## Research, Knowledge and Information :

### Evaluate the following expression using the value... - OpenStudy

Evaluate the following expression using the values given: ... Find 3x2 - y3 - y3 - z if x = 3, y = -2, and z = -5.\[3x^2-y^3-y^3-z\] ... Find 3x2 - y3 - y3 - z if x ...

### Evaluate the following expression using the values given ...

Evaluate the following expression using the values given: Find 3x2 − y3 − y3 − z if x = 3, y = −2, and z = −5. Numerical Answers Expected!

### Evaluate the following expression using the values given ...

Evaluate the following expression using the values given: Find 3x2 - y3 - y3 - z if x = 3, y = -2, and z = -5. weegy; Answer; Search; More; ... Find 3x2 - y3 - y3 - z ...

### View question - Evaluate the following expression using the ...

Evaluate the following expression using the values given: Find 3x2 - y3 - y3 - z if x = 3, y = -2, and z = -5. 0 . ... Find 3x2 - y3 - y3 - z if x = 3, y = -2, ...

### Part 1 1. Evaluate the following expression using the values ...

Evaluate the following expression using the values ... Find 3x2 y3 y3 z if x = 3, y = 2, and z = 5. ... 2x3 + 3y2 − 17 when x = 3 and y = 4. 3. Evaluate the ...

### I just recieved this question on homework and hav... - OpenStudy

I just recieved this question on homework ... Evaluate the following expression using the values given: Find 3x2 - y3 - y3 - z if x = 3, y = -2, and z = -5 ...

### How do you find x - 3y if x = 3 and y = -2? | Socratic

9 substitute the values x = 3 and y = - 2 into the expression x - 3y rArr 3 -3 (- 2 ) = 3 + 6 = 9 -3( -2 ) ... How do you find x - 3y if x = 3 and y = -2? Algebra ...

## Suggested Questions And Answer :

### Given the function defined by t(x) = x3 – 3x2 + 2x – 3, find t(10).

????????????????? yu wanna EVALUATE  a funkshun at x=10 ?????????????

### Evaluate ;Find 3x2 - y3 - y3 - z if x = 3, y = -2, and z = -5.

????????????? "3x2" ????? maebee that shood be 3*x ??? or maebee 3*x^2 ?????

### Find the values of A, B, C, D, and E by evaluating 3x2 + x + 1 at x = 2 based on the given algorithm.Working through each step of the algorithm is shown below:

http://web.cs.ucdavis.edu/~ma/ECS20/hw4-sol.pdf

### Evaluate the derivative at the given value of x: If y = x^4 +4x^3 – 2x +2, find dy/dx |x = -1

Evaluate the derivative at the given value of x: If y = x^4 +4x^3 – 2x +2, find dy/dx |x = -1 dy/dx = 4x^3 + 12x^2 - 2 dy/dx(-1) = 4(-1)^3 + 12 (-1)^2 - 2                = -4 + 12 - 2 = 6

### evaluate the given funtion. f(x)=2x+4; find f(3x)-3f(x)

Question: evaluate the given funtion. f(x)=2x+4; find f(3x)-3f(x) . f(3x) = 2(3x) + 4 = 6x + 4 3f(x) = 3(2x + 4) = 6x + 12 f(3x) - 3f(x) = 6x + 4 - 6x - 12 = -8 Answer: f(3x) - 3f(x) = -8

### volume of a solid generated by revolving area bounded by the curves about the indicated axis?

(a) The picture shows the given curve and line. The line PQ shows the height of a cylinder where P is a point on the curve. The cylinder is the result of rotating the line PQ about the y-axis as the axis of rotation (x=0). The line and curve intersect when x=6x-x^2, that is, x(5-x)=0 at x=0 and 5. The cylinder is hollow with an infinitesimally thin wall, thickness dx. The radius of the cylinder is x, the height of the cylinder is 5x-x^2 as can be seen by the geometry, and the area of this cylindrical shell is found by "rolling out" the cylinder into a rectangular lamina. So the length of the rectangle is 2πx, the circumference of the cylinder, and the height 5x-x^2, making the area 2πx^2(5-x). The volume of the cylinder is the area multiplied by the thickness dx: 2πx^2(5-x)dx. The sum of the volumes of the cylindrical shells gives us the volume of rotation of the shape bounded by the line and curve. This sum is ∫(2πx^2(5-x)dx) between the limits x=0 to 5. The integral evaluates to 2π(5x^3/3-x^4/4) and, applying the limits: 2π(625/3-625/4)=625π/6=327.25 cu units approx. (b) This time we have a cylinder radius 4-x and height PR=2√(4-x)-4+x. The volume of the cylindrical shell is 2π(4-x)(2√(4-x)-4+x)dx and the integral ∫(2π(4-x)(2√(4-x)-4+x)dx). Since y=4-x we can replace 4-x with y and dx by -dy. The integral becomes -2π∫(y(2√y-y)dy). Since x=4-y and x=(16-y^2)/4 we can write 4-y=(16-y^2)/4 and solve for y. 16-4y=16-y^2 so y(4-y)=0 and y=0 and 4 as evidenced in the picture. The limits are 4≥y≥0. The minus on the integral is changed to plus if we reverse the limits for y. So we need to evaluate the definite integral: 2π∫((2y^(3/2)-y^2)dy)=2π[(4/5)z^(5/2)-z^3/3] for 0≤y≤4. This evaluates to 2π(128/5-64/3)=128π/15=26.81 cu units approx. (c) The intersection point between the parabola and line y=4 is given by 16=8x, so x=2 and y=4: (2,4). The parabola meets the y-axis (x=0) at the origin (0,0). For a point P(x,y) on the parabola 4-y is the radius of a disc of thickness dx and therefore the volume of the disc is π(4-y)^2dx=π(16-8y+y^2)dx. Since y^2=8x we can evaluate the integral π∫((16-16√(2x)+8x)dx) for 0≤x≤2 to find the volume of revolution around the line y=4. This evaluates to 8π[2x-4√2x^(3/2)/3+4x^2] for 0≤x≤2=8π(4-16/3+16)=352π/3=368.61 cu units.

### can you please explain how to to find dy/dx for the function x^2 y+ Y^2 x = -2

I need to find dy/dx of this function and evaluate the derivative at the point (2,-1) x^2 y+y^2 x = -2 solve the equation to be  = 0 x^2y + y^2x +2 = 0 find partial derivatives for dy and dx, the first term has two parts x^2y has two partial derivatives 2xy dx + x^2 dy the second term has 2 parts y^2x has 2 partial derivatives y^2 dx + 2yx dy and 2 has no derivative 2xy dx + y^2 dx + x^2 dy + 2yx dy = 0 2xy + y^2 dx = (-x^2 - 2xy) dy dy/dx = (2xy + y^2)/(-x^2 - 2xy) use the point (2,-1) dy/dx = [2*2*(-1) + (-1)^2]/[-1(2)^2 -2*2*(-1)] dy/dx = (-4 + 1) / (-4 + 4)  there is a 0 in the de=nominator therefore it is undefined

### Evaluate the function for f(x) = 3x2 + 1 and g(x) = x − 3. (fg)(−4)

Evaluate the function for f(x) = 3x2 + 1 and g(x) = x − 3. (fg)(−4)   f(x) = 3x2 + 1 and g(x) = x − 3.   fg = 3(x – 3)2 + 1   (fg)(−4) fg(-4) = 3(-4 – 3)2 + 1 fg(-4) = 3(-7)2 + 1 fg(-4) = 3*49 + 1 fg(-4) = 147 + 1 fg(-4) = 148

### evaluate the logarithm log8 8

I think that what you mean is: evaluate the logarithm of 8 where the logarithm is taken to the base 8. Definition: The logarithm of a number, to a particular base, is the power to which the base must be taken in order to give the given number. i.e. Logb n = p  where   b^p = n Since we have to find the log of the number 8, where the log is taken to the base of 8, then we need to find a power, p, such that 8 (the base) taken to the power, p, will equal the given number, 8. i.e. we need to find p such that 8^p = 8 The answer is obviously p = 1